Absence of a significant interaction of two common NOS1 and 5-HTT polymorphisms on sensorimotor gating in humans - Rovný, R; Marko, M; Minárik, G; Riečanský, I (Physiological research, 2021)
The neurotransmitter serotonin has been critically implicated in the pathogenesis of several mental disorders. The serotonin transporter (5-HTT) is a key regulator of serotonergic neurotransmission and its genetic variability is associated with increased risk of psychopathology. One well known polymorphic locus in the 5-HTT gene affecting its expression is a tandem repeat in the promoter region (5-HTTLPR). It has been reported that 5-HTT is functionally coupled with the neuronal nitric oxide synthase (NOS1 or nNOS), an enzyme catalyzing the production of nitric oxide (NO). We have previously demonstrated that a tandem repeat polymorphism in the promoter of NOS1 exon 1f (Ex1f-VNTR) is associated with sensorimotor gating, a marker of inhibitory processing and a well established endophenotype of several neuropsychiatric disorders. Here we investigated the combined genetic effects of NOS1 Ex1f-VNTR and 5-HTTLPR on sensorimotor gating, measured by prepulse inhibition (PPI) of the acoustic startle reflex, in 164 healthy adults. We found no evidence for the interaction between NOS1 Ex1f-VNTR and 5-HTTLPR on PPI. PPI was associated with NOS1 Ex1f-VNTR, but not 5-HTTLPR. Our data suggest that while NOS1 plays a role in sensorimotor gating, the nitrergic pathway of gating regulation does not involve the action of 5-HTT.
Keywords: Polymorphism, Single Nucleotide; exony; Humans; Promoter Regions, Genetic; senzorimotorický kortex; Serotonin Plasma Membrane Transport Proteins; prepulsní inhibice; jednonukleotidový polymorfismus; Female; synthasa oxidu dusnatého, typ I; mladý dospělý; dospělí; Reflex, Startle; Phenotype; Exons; Genotype; lidé; Minisatellite Repeats; minisatelitní repetice; Adult; úleková reakce; ženské pohlaví; Male; membránové transportní proteiny pro serotonin; fenotyp; Nitric Oxide Synthase Type I; Young Adult; Sensorimotor Cortex; genotyp; Prepulse Inhibition; mužské pohlaví; promotorové oblasti (genetika)